Assessment of Variations in Growth, Bark thickness and Heartwood Content of Different Populations of Redsanders (Pterocarpus santalinus) in Karnataka - Durai, M. V. (Indian Forester, 2021)
Red sanders is one of the highly valued tree species in the world, native to south parts of Eastern Ghats (Andhra Pradesh and Tamil Nadu). As the success of any tree improvement depends upon the amount of variations found in heritable traits of populations and is basis for future genetic improvement, the present study was carried out to assess the variations in growth traits, bark, sap- and heartwood of different populations of red sanders in Karnataka. Hullikere (43 years), K.Settihalli (47 years), Jharakabande (32 years), Nallal (42 years), Yeshwanpur -A (42 years) and Yeshwanpur-B (42 years) in Karnataka. Significant variability found in growth traits viz., girth, straightness, tree height and sap- and heartwood content of the Red sanders. Time of heartwood formation varies within and between trees as well as between the populations. Both content and colour of heartwood vary even in the trees of same girth in a stand. No heartwood was found in trees which had girth <37, <41, <44, <46 and <48cm at breast height in Jharakabande, Hullikere and Yeshwanpur-B, Yeshwanpur A, Nallal and K.Settihalli plantations, respectively. The heartwood formation was not depicted any trend with tree size and age of trees in the Redsanders populations.